Assessment of Quality of Life of People Living with HIV and AIDS Receiving Anti-Retroviral Therapy in Kathmandu Valley - Acharya , DK (Journal of Institute of Medicine Nepal, 2014)
Introduction: Quality of Life (QOL) of people living with HIV and AIDS is a great concern. The impact of HIV on QOL falls under four major domains referred to as physical, psychological, social and environment domain. The objective of this study was to assess the quality of life of people living with HIV and AIDS taking antiretroviral therapy and its association with socio demographic and disease related variables. Methods: Descriptive cross sectional study design was used. 128 randomly selected participants enrolled at Tribhuwan University Teaching Hospital (TUTH) ART center above 15 years were interviewed. QOL was evaluated using the World Health Organization Quality of Life (WHOQOL) Bref instrument. Data was entered in Epi Data and analyzed using SPSS version 16. Results: The median scores with interquartile range (IQR) in four domains of QOL was highest in social domain i.e. 69 (56 to 75) and lowest in psychological domain i.e. 56 (50 to 69). All the domains were positively correlated with the overall QOL with Spearman’s rho ranging from .31 to .63. Strongest correlation was observed between psychological domain and overall QOL. Age, sex and marital status were significantly associated with the overall QOL whereas level of education and disease related variables i.e. CD4 counts and WHO clinical stage have no significant association with overall QOL. Conclusion: The study concludes the need for psychological support and community based interventions for PLHIV and AIDS to enhance their QOL. Social support to women living with HIV and AIDs is also required to help them better cope with the disease.